1979
DOI: 10.1679/aohc1950.42.481
|View full text |Cite
|
Sign up to set email alerts
|

Formation and release of secretory granules during mitosis in the anterior pituitary gland.

Abstract: Summary. Electron microscopic images indicating exocytosis of secretory granules were obtained in rat prolactin cells undergoing mitosis at the estrus in the female reproductive cycle. Immature secretory granules looking like small cored vesicles were found among chromosomes and microtubules of the mitotic spindle. Golgi apparatus was fragmented and its small elements mostly consisting of vesicles were seen at the peripheral region of the cell. Rough endoplasmic reticulum was mostly vesiculated, but lamellar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Still a further possibility is that the responsiveness of the hypothalamo-pituitary glands to sex steroids is low until 30 days of age in our rats. With regard to the last possibility, there was a report suggesting that some maturational period was necessary until the estrogenic control on prolactin secretion became substantially effective [Ojeda and McCann, 1974;Ojeda et al, 1977], Mitotic prolactin cells were previously reported in estrogen-treated rats [Zam brano and Deis, 1970] or in intact adult rats [Kurosumi, 1971[Kurosumi, , 1979. The present study on developing pituitaries also showed the presence of mitotic prolactin cells, and that mitotic prolactin cells were more numerous in female rats than in males at adult ages.…”
Section: Discussionsupporting
confidence: 65%
“…Still a further possibility is that the responsiveness of the hypothalamo-pituitary glands to sex steroids is low until 30 days of age in our rats. With regard to the last possibility, there was a report suggesting that some maturational period was necessary until the estrogenic control on prolactin secretion became substantially effective [Ojeda and McCann, 1974;Ojeda et al, 1977], Mitotic prolactin cells were previously reported in estrogen-treated rats [Zam brano and Deis, 1970] or in intact adult rats [Kurosumi, 1971[Kurosumi, , 1979. The present study on developing pituitaries also showed the presence of mitotic prolactin cells, and that mitotic prolactin cells were more numerous in female rats than in males at adult ages.…”
Section: Discussionsupporting
confidence: 65%
“…Before electron-microscopic immunocytochemistry became routine, Kurosumi et al (Kurosumi and Kobayashi 1966;Kurosumi 1971Kurosumi , 1979) observed mitosis of pituitary cells, whose cytoplasm contained many secretory granules, in the rats after removal of the target organ or in female rats during estrus.…”
Section: Studies On the Proliferation Of Pituitary Cells Identified Bmentioning
confidence: 99%
“…A further study by electron microscopy (Kurosumi, 1979) demonstrated not only the production of secretory granules but also the release of granules by exocytosis during mitosis (Fig. 5e,f).…”
Section: Lysosome Multivesicular Bodymentioning
confidence: 73%